Design and fabrication of flatbread dough maker / Muhammad Iskandar Ahmad Zulfaqar and Nurrul Amilin Zainal Abidin - Ahmad Zulfaqar, Muhammad Iskandar; Zainal Abidin, Nurrul Amilin (School of Mechanical Engineering, 2023)
Flatbreads were amongst the earliest processed foods, made throughout most of the world, where the grains are mashed into a paste or flour and then baked into a flatbread. Flatbreads traditionally ranging from one millimeter thick to a few centimeters thick so that they can be easily consumed. To date, there are still people using hand to make the flatbread dough for their business. The work of making flatbread dough are often time consuming and arduous, despite the simple process to make the dough. The available dough machine in the market are often small and thus not suitable for a large-scale business purpose. The dough maker usually can fit up to 1-2 kilogram of flour, and thus the process must be repeated few times before the desired output of dough is produced. Therefore, it is aims of this study design and fabricate a flatbread dough machine that can fit up to 5 kilograms of flour, aids in reducing the time consuming to make the flatbread dough and less taxing. The proposed machine will make use the concept and working principle of bicycle, where user will have to pedal the blade equipped in the front part by means of chain. Pedaling the cycle will make the blade rotating, thus kneading the flour until the desired dough is produced. The proposed machine is affordable, friendly user and can fit up to 5 kilograms per cycle and less taxing as the working principle is based on cycling mechanism.